2016
DOI: 10.18632/oncotarget.7593
|View full text |Cite
|
Sign up to set email alerts
|

CD274/PD-L1gene amplification and PD-L1 protein expression are common events in squamous cell carcinoma of the oral cavity

Abstract: Immunomodulatory therapies, targeting the immune checkpoint receptor-ligand complex PD-1/PD-L1 have shown promising results in early phase clinical trials in solid malignancies, including carcinomas of the head and neck. In this context, PD-L1 protein expression has been proposed as a potentially valuable predictive marker. In the present study, expression of PD-L1 and PD-1 was evaluated by immunohistochemistry in 80 patients with predominantly HPV-negative oral squamous cell carcinomas and associated nodal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
141
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 48 publications
(56 reference statements)
17
141
7
Order By: Relevance
“…The expression of PD-L1 in this patient was comparable to that in other genitourinary cancer types, such as bladder cancer (20%) (25), and non-genitourinary cancer types, such as breast cancer (23.4%) (26), colorectal cancer (36%) (27), testicular seminomas (73%) (28) and cancer of the oral cavity (73%) (29). The PD-1/PD-L1 axis has a notable role in the immune antitumor response (30,31).…”
Section: Discussionsupporting
confidence: 54%
“…The expression of PD-L1 in this patient was comparable to that in other genitourinary cancer types, such as bladder cancer (20%) (25), and non-genitourinary cancer types, such as breast cancer (23.4%) (26), colorectal cancer (36%) (27), testicular seminomas (73%) (28) and cancer of the oral cavity (73%) (29). The PD-1/PD-L1 axis has a notable role in the immune antitumor response (30,31).…”
Section: Discussionsupporting
confidence: 54%
“…PD-L1 is also over-expressed in cancer cells under the influence of oncogenic mutations, such as Phosphatase and tensin homologue (PTEN) loss or Nucleophosmin-anaplastic lymphoma kinase (NPM/ALK) [28, 29]. Amplification at 9p24.1, where PD-L1 resides, has been associated with PD-L1 up-regulation in squamous cell oral carcinoma [30] and non-small cell lung cancer [31]. The activation of the PI3K pathway in response to PTEN loss in both breast cancers [32] and glioblastomas [28] induces PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recently, it has been shown that ~ 20% of patients with triple-negative breast cancer respond to PD-1 blockade with pembrolizumab. 24 Chromosome 9p24.1 amplification appears to be a recurrent event across several tumour types and further studies will need to be performed to assess its value as a biomarker for response to PD-1 blockade.…”
Section: Discussionmentioning
confidence: 99%